Role of extracellular vesicles in nonalcoholic fatty liver disease - Jiang, Wei; Xu, Youhui; Chen, Jou-Chen; Lee, Yi-Hung; Hu, Yushin; Liu, Chang-Hai; Chen, Enqiang; Tang, Hong; Zhang, Hua; Wu, Dongbo (Frontiers in Endocrinology, 2023)
Background: Nonalcoholic fatty liver disease (NAFLD) is a common chronic liver disease that affects approximately one-quarter of the global population and is becoming increasingly prevalent worldwide. The lack of current noninvasive tools and efficient treatment is recognized as a significant barrier to the clinical management of these conditions. Extracellular vesicles (EVs) are nanoscale vesicles released by various cells and deliver bioactive molecules to target cells, thereby mediating various processes, including the development of NAFLD. Scope of review: There is still a long way to actualize the application of EVs in NAFLD diagnosis and treatment. Herein, we summarize the roles of EVs in NAFLD and highlight their prospects for clinical application as a novel noninvasive diagnostic tool as well as a promising therapy for NAFLD, owing to their unique physiochemical characteristics. We summarize the literatures on the mechanisms by which EVs act as mediators of intercellular communication by regulating metabolism, insulin resistance, inflammation, immune response, intestinal microecology, and fibrosis in NAFLD. We also discuss future challenges that must be resolved to improve the therapeutic potential of EVs. Major conclusions: The levels and contents of EVs change dynamically at different stages of diseases and this phenomenon may be exploited for establishing sensitive stage-specific markers. EVs also have high application potential as drug delivery systems with low immunogenicity and high biocompatibility and can be easily engineered. Research on the mechanisms and clinical applications of EVs in NAFLD is in its initial phase and the applicability of EVs in NAFLD diagnosis and treatment is expected to grow with technological progress.